Doxorubicin derivative loaded acetal-PEG-PCCL micelles for overcoming multidrug resistance in MCF-7/ADR cells. (2nd September 2019) - Zhong, Xin-Cheng; Xu, Wen-Hong; Wang, Zi-Ting; Guo, Wang-Wei; Chen, Jie-Jian; Guo, Ning-Ning; Wang, Tian-Tian; Lin, Meng-Ting; Zhang, Zhen-Tao; Lu, Yi-Ying; Yang, Qi-Yao; Han, Min; et al.
Abstract: Objective: This study was aimed to develop DOX-TPP loaded acetal-PEG-PCCL micelles to improve the clinical efficacy of drug resistance tumor. Significance: Chemotherapy is one of the main treatments for breast cancer but is plagued by multidrug resistance (MDR). DOX-TPP-loaded micelles can enhance the specific concentration of drugs in the tumor and improve the efficacy and overcome MDR. Methods: In this study, DOX-TPP-loaded micelles based on acetal-PEG-PCCL were prepared and their physicochemical properties were characterized. The cellular uptake and ability to induce apoptosis of the micelles was confirmed by flow cytometry in MCF-7/ADR cells. In addition, cytotoxicity of the micelles was studied in MCF-7 cells and MCF-7/ADR cells. Confocal is used to study the subcellular distribution of DOX. Free DOX-TPP or DOX-TPP-loaded acetal-PEG-PCCL micelles were administered via intravenous injection in the tail vain for the biodistribution study in vivo. Results: The diameter of micelles was about 102.4 nm and their drug-loading efficiency is 61.8%. The structural characterization was confirmed by 1H NMR. The micelles exhibited better antitumor efficacy compared to free doxorubicin in MCF-7/ADR cells by MTT assay. The apoptotic rate and the cellular uptake of micelles were significantly higher than free DOX and DOX-TPP. Micelles can efficiently deliver mitochondria-targeting DOX-TPP to tumor cells. The result of bio-distribution showed that the micelles had stronger tumor infiltration ability than free drugs. Conclusions: In this study, mitochondriotropic DOX-TPP was conjugated to the nanocarrier acetal-PEG-PCCL via ionic interaction to form a polymer, which spontaneously formed spherical micelles. The cytotoxicity and cellular uptake of the micelles are superior to free DOX and exhibit mitochondrial targeting and passive tumor targeting, indicating that they have potential prospects.